Olhares Irreverentes de Natália Correia e Hilda Hilst na Focagem Autobiográfica - Dias, Maria Heloisa Martins [UNESP] (Edizioni Ca Foscari, 2020)
This article explores two talented, controversial writers. One Portuguese, the other Brazilian, both fueled by irreverence and provocation in the way they focus on themselves and the world. Natália Correia, a poet, novelist and Azorean playwright (1923-93), whose work emerged in the midst of the Salazar regime, and with a militant political-literary performance with other leading figures in Portuguese culture and literature during the 1950s and 1960s. Her poetry maintains affinities with aesthetic tendencies of Surrealism, although she was not a strict follower of any literary movement. Hilda Hilst, a poet, prose and playwright from São Paulo (1930-2004), was a militant of different nature. She was not linked to any aesthetic programs or literary trends, a singularity that even today defies critics.
Irreverent views of Natália Correia and Hilda Hilst from an autobiographical perspective
Keywords: Hilda Hilst; Natália Correia; Poetry; Spirituality; Trauma